Development of a label-free plasmonic gold nanoparticles aggregates sensor on the basis of charge neutralization for the detection of zearalenone. (15th February 2022) - Xing, Keyu; Peng, Juan; Chen, Wenyao; Fang, Bolong; Liu, Daofeng; Shan, Shan; Zhang, Ganggang; Huang, Yina; Lai, Weihua
Graphical abstract: Highlights: AuNPs aggregates could be rapidly formed based on charge neutralization. The electrostatic repulsion between AuNP aggregates prevents further aggregation. The strategy eliminates the instability of salt-induced AuNPs aggregates. A label-free dual-channel sensing strategy was applied to detect zearalenone. Abstract: Mycotoxin contamination of corn has been considered a serious problem because it can accumulate in different organs or tissues via ingestion or skin contact and cause several health problems in humans. We have constructed a label-free, colorimetric, and fluorescence dual-channel sensing platform for the detection of zearalenone. Here, we demonstrate that plasmonic gold nanoparticles aggregates could be rapidly formed on the basis of charge neutralization by positively charged SYBR Green I. The sensing platform allowed quantitative detection as low as 0.89 μg kg −1 and visual detection as low as 2.5 μg kg −1 . The charge neutralization strategy eliminates a major source of instability in conventional gold nanoparticles colorimetric measurements and paves the way for accurate, label-free bioanalysis.